KEMAMPUAN BERPIKIR KREATIF DAN KEMANDIRIAN BELAJAR DENGAN PENDEKATAN OPEN-ENDEED PADA MATERI POLINOMIAL - Dewi Adharini (Direktorat Guru Pendidikan Menengah dan Pendidikan Khusus, 2022)
This study aims to determine the ability to think creatively and learn independently on Polynomial material using an open-ended approach in semester 2 of the 2020/2021 academic year in class XI MIPA7 SMA Negeri 6 Cimahi. The method used in this research is Classroom Action Research (CAR) which consists of two cycles. The implementation of the research starts on February 16, 2021 until May 19, 2021. Cycle I with the sub-themes of dividing polynomials and the remainder theorem is carried out in 4 meetings and ends with tests and filling out a self regulated learning questionnaire; Cycle II with the factor theorem sub-theme was carried out in 2 meetings and ended with a test and filling out a self regulated learning questionnaire. The subjects in this study consisted of 36 students consisting of 24 women and 12 men. Data collection techniques were carried out by using online tests using the Learning Management System (LMS) at school.id and non-tests, namely a questionnaire about learning independence using google form. The data analysis technique is descriptive quantitative. The results showed that learning with an open-ended approach was able to improve creative thinking skills from an average score of 73 in the first cycle to 74 in the second cycle. Independent learning from the mean score of 88 in the first cycle decreased to 87 in the second cycle. Thus, the open-ended approach to polynomial material can improve creative thinking skills but has not been able to increase the learning independence of students in class XI MIPA 7 SMA Negeri 6 Cimahi.